A nanomaterial integrated technology approach to enhance the energy-water-food nexus. (July 2021) - Okonkwo, Eric C.; Abdullatif, Yasser M.; AL-Ansari, Tareq
Abstract: This study reviews the potential of nanomaterials to enhance the performance of the energy-food-water (EWF) nexus in regions that have a disproportionate distribution of resources. The review study highlights the interlinkages that exists between the resources within the nexus and discusses a nexus-based approach to solving the individual resource needs of arid regions. An EWF nexus-based assessment of the state of Qatar (as a case study) is conducted, and several response options that utilise nanomaterials and sustainable energy technologies to improve the overall performance of the nexus are proposed. Based on the needs of the selected case study, an integrated renewable energy-based solution to the key nexus needs for arid regions is proposed. A solar-powered multigeneration system operating with copper-based nanofluid in the solar collector is thermodynamically analysed, and the result demonstrates that the system that produces power, freshwater, and cooling for greenhouse farming has energy and exergy efficiencies of 19% and 16.4% respectively. The deployment of the multigeneration system would lead to a reduction in greenhouse gas emissions at a rate of 1111 kg/h for CO2, 4.52 kg/h for NOX, and 8.95 kg/h for SOX . An assessment of the proposed system illustrates that the key resources of the nexus can be met sustainably when renewable energy is integrated into the energy mix in the region. The study concluded that a nexus-based solution to the energy, food, and water challenges would not only lead to improved resource efficiency, but has the potential to decrease the carbon footprint of the region. Highlights: Potential of nanomaterials to enhance the performance of the energy food and water nexus. Presents an assessment and response option for the EWF nexus in the state of Qatar. Proposes a multigeneration system using copper-based nanofluid in the solar collector. The proposed system reduced emissions by 1111 kg/h of CO2, 4.52 kg/h of NOX, and 8.95 kg/h of SOX . A nexus based solution to EWF challenges would lead to improved resource efficiency.